2021
DOI: 10.1002/ece3.7962
|View full text |Cite
|
Sign up to set email alerts
|

Burrow webs: Clawing the surface of interactions with burrows excavated by American badgers

Abstract: Ecosystem engineers are organisms that influence their environment, which includes alterations leading to habitat provisioning for other species. Perhaps the most well‐examined guild of species provisioning habitat for other species is tree cavity excavators or woodpeckers (Picidae). Many studies have examined the suite of secondary cavity users that rely on woodpeckers, and how the ecological network of secondary users, collectively referred to as the nest web, changes across communities. Despite similar habi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Small semi-fossorial herbivores can affect soil properties by burrowing tunnels ( Nicod et al, 2020 ; Andersen et al, 2021 ), excreting feces and urine ( Clark et al, 2016 ; Cui et al, 2020 ; Zhang et al, 2020 ), and redistributing the soil ( Davidson et al, 2012 ; Guo et al, 2012 ; Pang et al, 2020a ). Previous studies have shown that small semi-fossorial herbivores can decrease SBD ( Dobson et al, 1998 ; Wilson and Smith, 2015 ) and soil moisture ( Pang and Guo, 2017 ) and increase the soil nitrogen concentration ( Liu et al, 2013 ; Yu et al, 2017a ; Mallen-Cooper et al, 2019 ; Cui et al, 2020 ) and soil organic carbon (SOC) ( Clark et al, 2016 ; Pang et al, 2019 ) in grasslands.…”
Section: Introductionmentioning
confidence: 99%
“…Small semi-fossorial herbivores can affect soil properties by burrowing tunnels ( Nicod et al, 2020 ; Andersen et al, 2021 ), excreting feces and urine ( Clark et al, 2016 ; Cui et al, 2020 ; Zhang et al, 2020 ), and redistributing the soil ( Davidson et al, 2012 ; Guo et al, 2012 ; Pang et al, 2020a ). Previous studies have shown that small semi-fossorial herbivores can decrease SBD ( Dobson et al, 1998 ; Wilson and Smith, 2015 ) and soil moisture ( Pang and Guo, 2017 ) and increase the soil nitrogen concentration ( Liu et al, 2013 ; Yu et al, 2017a ; Mallen-Cooper et al, 2019 ; Cui et al, 2020 ) and soil organic carbon (SOC) ( Clark et al, 2016 ; Pang et al, 2019 ) in grasslands.…”
Section: Introductionmentioning
confidence: 99%
“…Burrow creation is a facilitative interaction whereby commensal species exploit resources offered from burrows, including the provision of shelter from predators and extreme conditions, as well as foraging and breeding opportunities. For instance, American Badger ( Taxidea taxus ) burrows are exploited by 31 species, including numerous mammal species that use the burrows for shelter ( Andersen et al 2021 ). Similarly, Gopher Tortoise ( Gopherus polyphemus ) burrows are used by over 60 vertebrate species ( Dziadzio and Smith 2016 ), and Giant Armadillo ( Priodontes maximus ) burrows are visited by over 50 vertebrate species ( Desbiez and Kluyber 2013 ).…”
mentioning
confidence: 99%